1994
DOI: 10.1159/000168693
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Renal Effect of Cisplatin in Man

Abstract: Although the acute nephrotoxicity of cisplatin has been well documented, long-term follow-up studies are scanty. We have evaluated the renal function in 35 patients who have had completed therapy with cisplatin at least 3 months before the study. All patients had normal serum creatinine levels before chemotherapy. Evaluation of renal function included: serum creatinine, glomerular filtration rate (inulin clearance), effective renal plasma flow (p-aminohippurate clearance), urinary Β2-microglobulin a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
34
1
1

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 10 publications
2
34
1
1
Order By: Relevance
“…Our study, which included a greater diversity of tumor types, supports this initial decline in eGFR. In previous studies in which GFR and renal plasma flow were measured using exogenous filtration markers and 24-hour creatinine clearance, the observed acute and chronic declines in GFR were of larger magnitude, ranging from 12% to 23% (12,13,15,(20)(21)(22). In our study, a lower median decline in eGFR of 10 ml/min per m 2 was observed.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Our study, which included a greater diversity of tumor types, supports this initial decline in eGFR. In previous studies in which GFR and renal plasma flow were measured using exogenous filtration markers and 24-hour creatinine clearance, the observed acute and chronic declines in GFR were of larger magnitude, ranging from 12% to 23% (12,13,15,(20)(21)(22). In our study, a lower median decline in eGFR of 10 ml/min per m 2 was observed.…”
Section: Discussionmentioning
confidence: 94%
“…Whether patient age at the time of onset of cisplatin treatment correlates with the incidence of AKI and long-term renal function is not well established. Some studies report a negative correlation between age and renal function (12,24,25), and others show no relationship (26). A possible explanation for this finding is that older patients had more subclinical renal injury that was not detected by SCr values compared with younger ones or that they may have other comorbidities that made them more susceptible to AKI from cisplatin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, limited data are available on long-term nephrotoxicity in testicular cancer survivors. The previous studies showed a 20-30% reduction in the GFR; however, most of these studies suffered from small sample sizes and relatively short-term follow-up periods; [7][8][9][10][11][12] this might be partly because GFR measurement is cumbersome. In addition, differences in the methods for GFR evaluation used in the studies make it difficult to interpret each result.…”
Section: Introductionmentioning
confidence: 99%